Effects of human recombinant growth hormone on exercise capacity, cardiac structure, and cardiac function in patients with adult-onset growth hormone deficiency. (December 2017) - Gonzalez, S; Windram, JD; Sathyapalan, T; Javed, Z; Clark, AL; Atkin, SL
Objective: Epidemiological studies suggest that adult-onset growth hormone deficiency (AGHD) might increase the risk of death from cardiovascular causes. Methods: This was a 6-month double-blind, placebo-controlled, randomised, cross-over trial followed by a 6-month open-label phase. Seventeen patients with AGHD received either recombinant human growth hormone (rGH) (0.4 mg injection daily) or placebo for 12 weeks, underwent washout for 2 weeks, and were then crossed over to the alternative treatment for a further 12 weeks. Cardiac magnetic resonance imaging, echocardiography, and cardiopulmonary exercise testing were performed at baseline, 12 weeks, 26 weeks, and the end of the open phase (12 months). The results were compared with those of 16 age- and sex-matched control subjects. Results: At baseline, patients with AGHD had a significantly higher systolic blood pressure, ejection fraction, and left ventricular mass than the control group, even when corrected for body surface area. Treatment with rGH normalised the insulin-like growth factor 1 concentration without an effect on exercise capacity, cardiac structure, or cardiac function. Conclusion: Administration of rGH therapy for 6 to 9 months failed to normalise the functional and structural cardiac differences observed in patients with AGHD when compared with a control group.